Kinerja Industri Kakao di Indonesia - Ening Ariningsih; Helena J Purba; Julia F Sinuraya; Sri Suharyono; Kartika Sari Septanti (Forum penelitian Agro Ekonomi, 2019)
Indonesia is among the largest cocoa producing countries in the world. Various policies for cocoa production and quality improvement has been issued, but it still deals with some constraints. This paper reviews cocoa Indonesia’s industry performance and its development strategy. Over the past decade, Indonesia’s cocoa production kept declining due to decreased mature crop areas, unproductive crops enhancement, lower yield, and conversion of cocoa fields. Cocoa plantation is dominated by smallholders, limited capital, less knowledge, lack of technology access, and restricted market information. Government’s role is crucial in facilitating efforts to increase productivity, quality, and markets access besides to developing its downstream industries. Developing cocoa industry is not only the responsibility of the Ministry of Agriculture but it involves other institutions, i.e., local governments, NGOs, businessmen, research institutions, and investors. It is expected to improve Indonesia’s cocoa competitiveness in international market. AbstrakIndonesia termasuk negara produsen kakao terbesar di dunia. Pemerintah telah berupaya mengeluarkan berbagai kebijakan untuk peningkatan produksi dan mutu kakao, namun pengembangan kakao di Indonesia masih mengalami berbagai masalah. Tulisan ini menganalisis kinerja industri kakao serta strategi pengembangannya di Indonesia melalui penelaahan literatur. Selama dekade terakhir produksi kakao Indonesia terus menurun karena berkurangnya luas areal tanaman menghasilkan, meningkatnya tanaman tidak produktif, penurunan produktivitas, dan konversi lahan kakao. Perkebunan kakao didominasi perkebunan rakyat skala kecil, bermodal terbatas, serta akses terbatas terhadap teknologi dan informasi pasar. Peran pemerintah sangat penting dalam fasilitasi upaya peningkatan produktivitas, mutu, akses pasar, serta pengembangan industri hilirnya. Upaya pengembangan kakao bukan hanya tanggung jawab Kementerian Pertanian, tetapi bersifat lintas sektoral. Peran serta pemerintah daerah, LSM, pelaku bisnis, lembaga penelitian, dan investor sangat besar untuk mengembangkan dan membenahi agribisnis kakao di Indonesia sehingga daya saingnya meningkat di pasar internasional.